2010
DOI: 10.1111/j.1365-294x.2010.04609.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic uniformity characterizes the invasive spread of water hyacinth (Eichhornia crassipes), a clonal aquatic plant

Abstract: Aquatic plant invasions are often associated with long-distance dispersal of vegetative propagules and prolific clonal reproduction. These reproductive features combined with genetic bottlenecks have the potential to severely limit genetic diversity in invasive populations. To investigate this question we conducted a global scale population genetic survey using amplified fragment length polymorphism markers of the world's most successful aquatic plant invader -Eichhornia crassipes (water hyacinth). We sampled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
135
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 184 publications
(137 citation statements)
references
References 60 publications
1
135
1
Order By: Relevance
“…A molecular study of clonal diversity in both the native and introduced range of E. crassipes supports this suggestion (28). For example, in the introduced range, 80% of the populations sampled contained a single clone, with one particular clone dominating in 74.5% of the populations sampled.…”
Section: Clonality In Plants With Sexual Polymorphismsmentioning
confidence: 50%
See 1 more Smart Citation
“…A molecular study of clonal diversity in both the native and introduced range of E. crassipes supports this suggestion (28). For example, in the introduced range, 80% of the populations sampled contained a single clone, with one particular clone dominating in 74.5% of the populations sampled.…”
Section: Clonality In Plants With Sexual Polymorphismsmentioning
confidence: 50%
“…For example, in the introduced range, 80% of the populations sampled contained a single clone, with one particular clone dominating in 74.5% of the populations sampled. Thus, a strong genetic bottleneck is associated with invasion, and the mid-styled morph dominates in most populations and the short-styled morph is entirely absent from the introduced range (23,28). The function of tristyly in promoting cross-pollination clearly differs in the two Eichhornia species as a result of their contrasting clonal strategies.…”
Section: Clonality In Plants With Sexual Polymorphismsmentioning
confidence: 99%
“…E. crassipes, seems to hold the exceptional ability to be invasive. This species has the potential to multiply aggressively through clonal means of reproduction, has high growth rate and a highly dispersive floating form [6] [7]. The ecological, social and economic impact of this invasive species is complex and multifaceted: it drastically affects the physical & chemical properties of the water by reducing temperature, pH, biological oxygen demand and nutrient level.…”
mentioning
confidence: 99%
“…Only one FGD in Bora, composed mainly of farmers involved in irrigated crop production (tomato, onion) around Ellen Lake, informed the plant to be useful in increasing soil fertility and used as cover plant for seedling establishment and during charcoal preparation. Although, our study did not include chemical composition analysis of the plant, studies elsewhere indicated that owing to its high alkalinity (pH>9) and potentially toxic heavy metals contents would restrict its use to flowering-plants, with no allowable application to horticulture for edible vegetables [16] which requires further investigation under our context.…”
Section: Community Perceptions Regarding Land Cover/use Changes and Cmentioning
confidence: 99%